The effects of wire diameter and an additional lateral wire on pin and tension-band fixation subjected to cyclic loads - Neat, B.; Kowaleski, M. P.; Litsky, A. S.; Boudrieau, R. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Despite reports of frequent complications, pin and tension-band wire remains the most common repair of simple olecranon fractures and osteotomies (1–5). A recent mechanical study found wire diameter to be the key determinant of pin and tension-band construct strength; models with 1.25-mm wire were much stronger than those with standard 1.0-mm wire exposed to single loads to failure (6). Additionally, fixation strength was also increased when a lateral wire was used in combination with a standard figure-ofeight wire. The purpose of the present study was to assess any advantages provided by 1.25-mm wire or an additional lateral wire over 1.0-mm wire for pin and tension-band fixation subjected to cyclic loading. Pin and tension-band fixation was applied to plastic olecranon osteotomy models with three wire configurations: 1.0-mm figure-of-eight, 1.25-mm figure-of-eight, and combined 1.0-mm figure-of-eight and lateral. Cyclic load was applied while caudal osteotomy displacement was measured with an extensometer. The three groups were compared in terms of cycles to failure, mean minimum displacement, mean maximum displacement, and mean displacement per cycle. Models with an additional lateral wire survived significantly more cycles than those with a solitary 1.0-mm figure-of-eight wire, although caudal osteotomy displacements were not significantly different. Conversely, models with 1.25-mm wire allowed significantly smaller minimum and maximum displacements than those with 1.0-mm wire, but did not survive significantly more cycles. It therefore appears that clinical use of 1.25-mm wire may improve stability, while use of an additional lateral wire may improve durability.
Keywords: Pin and tension-band wire; olecranon fixation; olecranon osteotomy; cyclic testing; Delrin.